Cloning of intronic sequence within DsRed2 increased the number of cells expressing red fluorescent protein - Pisal, Rishikaysh; Hrebíková, Hana; Chvátalová, Jana; Soukup, Tomáš; Filip, Stanislav; Mokrý, Jaroslav (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2017)
AIM: Cloning of artificial intronic sequence within the open reading frame (ORF) of DsRed2 gene. METHOD: Splice prediction software was used to analyze DsRed2 sequence to find an ideal site for cloning artificial intronic sequence. Intron was cloned within DsRed2 using cyclic ligation assembly. Flow cytometry was used to quantify the number of cells expressing red fluorescence. RESULT: Sequencing data confirmed precise cloning of intron at the desired position using cyclic ligation assembly. Successful expression of red fluorescence after cloning of intron confirmed successful intron recognition and splicing by host cell line. Cloning of intron increased the number of cells expressing red fluorescent protein. CONCLUSION: Cloning of intronic sequence within DsRed2 has helped to increase the number of cells expressing red fluorescence by approximately four percent.
Keywords: introny; HeLa Cells; Luminescent Proteins; transfekce; Transfection; otevřené čtecí rámce; klonování DNA; lidé; HeLa buňky; Open Reading Frames; luminescentní proteiny; Cloning, Molecular; Introns; Humans